A new early miocene species of Ophiocrossota (ophiuroidea) from Southern Patagonia, Argentina - Caviglia, Sergio (2007)
The first South American species of Ophiocrossota CLARK, 1928, O. kollembergorum n. sp., is described, extending the known geographical range of the genus to Argentina. The new species is characterized by its large radial shields, proximally in contact within, but separated distally by the triangular plates, and by its large and elongate oral shields, that cover most of the interradial area.